Peran Mahasiswa Program Asistensi Mengajar Dalam Meningkatkan Kompetensi Dan Adaptasi Teknologi SDN 1 Gondangkulon - Evi Wijayawati; Sediono (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
To cultivate superior human resources, higher education institutions play a key role in producing competitive graduates in the era of Industrial Revolution 4.0, which has now become a new paradigm in the education system. The *Merdeka Belajar-Kampus Merdeka* (MBKM) program, launched in 2020 and outlined in the Ministry of Education and Culture Regulation No. 3 of 2020, has fostered the development of flagship *Kampus Merdeka* programs. One such initiative, facilitated by the Ministry of Research, Technology, and Higher Education, is the Teaching Assistance program in educational institutions, known as the *Kampus Mengajar* program. Teaching Assistance is one of the key programs within the *Merdeka Belajar-Kampus Merdeka* (MBKM) curriculum. Its purpose is to empower students through collaboration with schools. In this program, students are tasked with supporting the teaching and learning process and aiding in technological adaptation. The partner school involved in the community service activities during the Teaching Assistance program is SDN 1 Gondangkulon, located in Gondangkulon Village, Gondang District, Nganjuk Regency, which holds a “B” accreditation. The scope of the Teaching Assistance Program covers teaching subjects such as Javanese Language and Cultural Arts, with a focus on literacy, creativity, and technological adaptation among students. Through this program, students are expected to develop leadership skills, build character, and gain valuable teaching experience. Additionally, since SDN 1 Gondangkulon faces a shortage of teaching staff, the program is also expected to improve the effectiveness of the learning process at the school.